Chapter Use of mixed study techniques in the evaluation of coastline dynamics - the "Porto Cesareo" MPA case of study - Picciolo, Andrea (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
The rise of the mean sea level is affecting negatively the entire coastal system, mainly due to the increase of the erosive phenomenon along the shorelines. We studied the erosion of a well knows tract of coastline, in a highly anthropized area, located inside an Italian Marine Protected Area. The methodology is based on mixed survey technics, drones aero photogrammetry surveys, aerial images acquired by the Italian Military Geographic Institute, elaboration of paleo-shorelines related to underwater archaeological markers, and on the elaboration of Sentinel-2 satellite products.